Understanding How Gender, Age, and Education Shape Mental Health Literacy Among Health Students at Universitas Muhammadiyah Surakarta - Devi, Annisa Andriana; Asyanti, Setia (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Mental health literacy is crucial for the well-being of every individual, including students. Given their vulnerability to mental health challenges, it is essential for students to develop a solid understanding of mental health. This study aimed to examine differences in mental health literacy and positive mental health literacy among health students at Muhammadiyah University of Surakarta (UMS), with respect to gender, age, and educational level.This research employed a comparative quantitative design. The population consisted of 5,125 UMS health students aged 18–25 years. A total sample of 210 students was selected using a quota sampling technique. Data were collected through an online questionnaire distributed via Google Forms and analyzed using ANOVA.The findings indicated no significant differences in mental health literacy across gender and age groups. However, significant differences were found based on educational level. Additionally, the results revealed no significant differences in positive mental health literacy across gender, age, or education. Overall, the categorization results suggest that health students at Muhammadiyah University of Surakarta possess a relatively high level of mental health literacy.